INTRA-ABDOMINAL HYPERTENSION AND INCREASED SERUM PROCALCITONIN LEVELS ARE IMPORTANT PROGNOSTIC MARKERS IN CRITICALLY ILL SURGICAL PATIENT’S OUTCOME: A PROSPECTIVE OBSERVATIONAL STUDY - Dutta, Divija; Prasad, Ram; Faisal, Mohd.; Porwal, Rekha (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study is to determine the clinical value of procalcitonin (PCT) levels and in recognizing surgical complications, morbidity and mortality in a heterogeneous group of general surgical patient population admitted in casualty ward and intensive care unit (ICU). Methods: A prospective, observational study was conducted on 100 patients by purposive sampling for blood and ascites in the peritoneal cavity, bowel distension and edema, high-volume resuscitation and massive transfusion, damage control surgery in traumatic patients, excessive tension after abdominal closure, post-operative ileus, circumferential abdominal eschar in burn patients, and hemodilution with severe sepsis were enrolled within 24 h of admission to the ICU or casualty ward in the Department of General Surgery, J.L.N. Medical College and Hospital, Ajmer, from August 2021 to December 2022. Results: The mean age of the overall patient population for the study is 52.29 years and it ranges between 16 years and 84 years. 79% of the patients presented with intra-abdominal hypertension (IAH), and mean serum PCT level in the IAH group is 4.47±7.49 which is higher than that in the non- IAH group (p<0.05). The mean serum PCT levels among the group having peritonitis as the cause of sepsis is 5.69 ng/mL and having pneumonitis as the cause of sepsis is 6.74 ng/mL (p=0.033). Conclusion: Serum PCT, a new serum biomarker for infection and inflammation, that has been found to be more sensitive and specific for the same, is also an indicator for patient mortality and morbidity, and also correlates with patient’s length of hospital stay can be said to have an important role in prediction of critically ill surgical patient’s outcome.